Controls on Spatial and Temporal Patterns of Slope Deformation in an Alpine Valley. Issue 12 (9th December 2021) - Oestreicher, N.; Loew, S.; Roques, C.; Aaron, J.; Gualandi, A.; Longuevergne, L.; Limpach, P.; Hugentobler, M.
Abstract: A comprehensive surface displacement monitoring system installed in the recently deglaciated bedrock slopes of the Aletsch Valley shows systematic reversible motions at the annual scale. We explore potential drivers for this deformation signal and demonstrate that the main driver is pore pressure changes of groundwater in fractured granitic mountain slopes. The spatial pattern of these reversible annual deformations shows similar magnitudes and orientations for adjacent monitoring points, leading to the hypothesis that the annually reversible deformation is caused by slope‐scale groundwater elevation changes and rock mass properties. Conversely, we show that the ground reaction to infiltration from snowmelt and summer rainstorms can be highly heterogeneous at local scale, and that brittle‐ductile fault zones are key features for the groundwater pressure‐related rock mass deformations. We also observe irreversible long‐term trends (over the 6.5 years data set) of deformation in the Aletsch valley composed of a larger uplift than observed at our reference GNSS station in the Rhone valley, and horizontal displacements of the slopes towards the valley. These observations can be attributed respectively to the elastic bedrock rebound in response to current glacier mass downwasting of the Great Aletsch Glacier and gravitational slope deformations enabled by cyclic groundwater pressure‐related rock mass fatigue in the fractured rock slopes. Plain Language Summary: Mountain ranges are subject to deformation due to tectonic forces, orogenesis, erosion, and gravity. Other factors can deform the slopes, such as atmospheric‐driven thermal expansion and contraction, freeze‐thaw in open fractures, and pore pressure variations. Close to retreating glaciers, the mechanical unloading of the ice body, and rapidly changing thermal and hydrologic conditions lead to deformation of the slopes. The difficulty resides in identifying the different factors contributing to the total deformation. We track surface displacements of fractured crystalline rock slopes adjacent to the Great Aletsch Glacier (Switzerland) tongue for more than six years at unprecedentedly high spatial and temporal resolutions. Our results demonstrate that groundwater is a critical driver of deformation. Centimetric reversible outward displacements are observed after the snowmelt season each year, followed by a seasonal recession to which are superimposed displacements caused by heavy rainfall‐recharge events. Fault zones can be key features where most of the hydromechanical deformation occurs, and their geometry can control the direction of deformation. Glacier melting induces long‐term trends of deformation. In addition, annual pore‐pressure cycles lead to hydromechanical fatigue processes. This work opens a new vision on the spatial and temporal variability of processes responsible for bedrock deformation in paraglacial mountain slopes. Key Points: Seasonal pore pressure variations in fractured crystalline hillslope induce correlated reversible surface deformations Decameter‐scale brittle‐ductile faults control local spatial variations of deformation patterns Cyclic groundwater pressure‐related rock mass fatigue induces irreversible gravitationally driven displacements in valley slopes